Position Control of 3-DOF Experimental Articulated Robot Arm using PID Controller - Vo, Dinh-Hieu; Le, Nam-Chau; Nguyen, Thi-Y-Nhi; Huynh, Tran-Phuong; Huynh, Nhat-Truong; Tran, Kim-Huy; Nguyen, Ba-Chinh; Do, Truong-Giang; Tran, Gia-Huy; Nguyen, Van-Dong-Hai (Journal of Fuzzy Systems and Control, 2025)
In this paper, we are simulating a 3-degrees of freedom (DOF) Articulated Robot Arm, calculating kinematics and building a PID controller for the 3-Dof Articulated Robot Arm. First, the design process of the 3-Dof robot arm model is done on the Solid works platform. Second, the PID control method is used to determine the "error" value which is the between the measured value of the variable parameter and the desired set value. The controller will minimize errors by adjusting the input control value. Finally, a real robot arm was controlled to move following the reference in the plane with the PID controller embedded on the Arduino microcontroller and collected data about the computer.